PENERAPAN ICE BREAKING UNTUK MENINGKATKAN MOTIVASI BELAJAR SENI BUDAYA SISWA KELAS XII DI SMA NEGERI 8 DENPASAR TAHUN PELAJARAN 2022/2023 - Gusti Ayu Made Puspawati; Gusti Made Karismanata (CV. ADIBA AISHA AMIRA, 2023)
Researchers, in this case students, under the direction of their supervisors, become substitute teachers in the subject of Cultural Arts at SMA Negeri 8 Denpasar in carrying out their duties in class XII. This study aims to determine students' learning motivation. Based on the observations, it is found that the motivation of students in participating in arts and culture lessons is still lacking. Based on these problems, researchers conducted research that had the aim of increasing motivation to learn Cultural Arts in Class XII by using ice breaker or also called Ice breaker. The method used in this research is observation and documentation. The type of research that researchers did was Classroom Action Research (PTK) which was carried out through 2 cycles. Each cycle consists of 4 stages, namely planning, implementation of action, observation and reflection. The research subjects were class XII using a sample of class XII MIPA 1 students, totaling 45 students consisting of 21 male students and 24 female students. Based on the results of classroom action research that has been carried out for two cycles by using ice breaking in learning Arts and Culture in class XII MIPA 1 SMA N 8 Denpasar shows an increase in student motivation in the learning process. This can be seen from the scores of students' learning motivation in the first cycle, which previously did not reach 80% of students who obtained learning motivation scores in the high category, in the first cycle of students who obtained high student learning motivation scores or ≥70 there were 20 students out of 45. In addition, the average score of students' learning motivation in cycle I was 75 in the high category. In cycle II there has been an increase in the observed aspects and indicators of success have been achieved, namely 90% of students get a learning motivation score of ≥70 in the very high category and there are still 2 students who get a score of ≤70. In addition, the average score of students' learning motivation in cycle II increased from 75 to 84 and the high category became very high.